Parents' preparations of their children for primary school :a survey in Kapit town - Chua,, Chai Ching. (Universiti Malaysia Sarawak, UNIMAS, 2009)
There are no prescribed ways on how parents prepare their children for primary school. However, most researchers have surveyed on perceptions of parents, teachers and the school authority on children readiness for school, and found varied views on how children should be ready for school. This study presents interview findings from 24 parents of Kapit Town regarding their preparations of children for primary school. The study seeks to find out how parents prepare their children for primary school by carrying out a survey in Kapit Town. For the purpose of this study, only three components of children’s needs are focused, they include physical needs, social-emotional needs and cognitive needs. Another objective is to identify factors influencing the preparations. Comparison in between three races, the Malay, the Iban and the Chinese as well as three income-levels are sought after. This study found that preparations on their children’s physical, social-emotional and cognitive needs are equally important to the respondents. Detailed examples are provided by respondents on how they prepare on the three domains. Background factors such as poverty and educational level of original family are the major influences on parents’ preparations. If compared to the Malay and Iban parents in this study, the Chinese respondents in this study have presented a tendency to emphasize more on preparing their children’s cognitive needs, while the lower income group of respondents have conveyed financial as a constraint for preparing their children for primary school.